Insults to religious feelings v. freedom of expression: Lessons from Aiisa’s case - Dimitry Gegenava (Studia z Prawa Wyznaniowego, 2022)
The present article aims to analyze selected aspects of the conflict between two basic values: freedom of expression and freedom of religion. Based on the co-called Aiisa’s case (see the judgement of the European Court of Human Rights of 22 July 2021, Ana Gachechiladze v. Georgia, App. No. 2591/19), the paper proposes general criteria for assessing insults to religious feelings. It is argued that national courts must not act as guardians of concrete religious groups or conventional morals, as this leads to negative results and destruction of the national law system. As a rule, it cannot be excluded that sacred images and figures are used in commercials or other ways of expression. When adjudicating on a case, every court should primarily consider the context, content and form, and prohibition of expression should be the last and final resort.